Te Film as a Saturable Absorber for the Mid-Infrared Er3+-Doped ZBLAN Fiber Laser - Zhang, Min; Kang, Liu; Ma, Zhijian; Yan, Peiguang; Hou, Shaodong (Frontiers in Physics, 2022)
We demonstrate a Q-switched Er3+-doped ZBLAN fiber laser at 2.8 µm mid-infrared (mid-IR) region achieved by adopting Te as the saturable absorber mirror (SAM). The modulation depth and saturation intensity of the Te-SAM were measured to be 7.2% and 10.81 MW/cm², respectively. Stable Q-switched laser pulses with the maximum pulse energy of 3.05 µJ and the minimum pulse width of 0.457 µs at the launched pump power of 4.51 W were obtained. Maximum average output power of 357 mW with repetition rate of 116.98 kHz were achieved. The signal-to-noise ratio (SNR) is 52 dB, which is higher than that of most 2.8 µm mid-infrared Q-switched fiber lasers reported so far. To the best of our knowledge, this is the first demonstration from a Q-switched fiber laser at 2.8 µm based on a Te-SAM.